Analisis Tingkat Kapabilitas Tata Kelola Teknologi Informasi pada Domain Deliver, Service and Support (DSS) Berdasarkan COBIT 2019: Systematic Literature Review - Muhammad Lutfi Ashari; Danendra Gustiarno; Yustian Servanda (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
Information Technology (IT) governance is crucial for coordinating technology use with the goals of the organization. Within the COBIT 2019 framework, the Deliver, Service and Support (DSS) sector is vital for guaranteeing efficient IT service delivery and maintaining operational stability. This research intends to evaluate and integrate the levels of IT governance capabilities found within the DSS sector, drawing on earlier research outcomes. A Systematic Literature Review (SLR) method was utilized, following the PRISMA guidelines. The literature was gathered from both national and international academic databases, covering publications from 2019 to 2025, and was chosen through phases of identification, screening, and quality evaluation. The findings show that many organizations reach Capability Level 2 (Managed) and Level 3 (Established), which suggests that their IT service procedures are typically organized and recorded, but they have not completely adopted practices for measuring performance and making continuous enhancements. The most common capability deficiencies are observed in DSS02 (Manage Service Requests and Incidents) and DSS05 (Manage Security Services), primarily due to insufficient documentation, minimal automation, and shortcomings in managing incidents and security. These results offer a thorough understanding of how DSS capabilities are implemented in different organizational areas and can act as a guide for enhancing IT service governance according to COBIT 2019.